Peningkatan hasil belajar tematik terpadu melalui model project based learning pada siswa sekolah dasar - Edi Cahyadi; Yari Dwikurnaningsih; Nurul Hidayati (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
Learning outcomes are abilities acquired by children through learning activities. Achiement of learning outcomes contains cognitive, and psychomotor. The Project Based Learning model is a learning model that is recognized by educators in 21st century integrated thematic learning where student-centered learning, in this study, researchers collaborated with the Project Based Learning model assisted by experiments. The purpose of the study was to improve integrated thematic learning of 5th grade elementary school student, theme 9 subtheme 1 dan 2. The type of research used was classroom action research. The results showed an increase in student learning outcomes from cycle 1 to cycle 2 using the Project Based Learning model.